First record of the genus Temnothorax Mayr, 1861 (Formicidae: Myrmicinae) in Hong Kong, with descriptions of two new species - Hamer, Matthew T.; Lee, Roger H.; Guénard, Benoit (European Journal of Taxonomy, 2023)
The ant genus Temnothorax Mayr, 1861 (Myrmicinae, Crematogastrini) is diverse with 498 species described. Species are distributed predominately within the northern hemisphere with species richness decreasing closer to the tropics; contrary to other ant genera overall. In Southeast Asia, richness is relatively low and knowledge on the genus remains fragmentary, likely due to poor sampling efforts compared to temperate regions. Here, using specimens from recent sampling efforts, Temnothorax is reported for the first time from the Hong Kong Special Administrative Region. Two new species, T. barrettoi Hamer & Guénard sp. nov. and T. haveni Lee, Hamer & Guénard sp. nov., are described based on qualitive morphological characters, with additional morphometric data also gathered. An updated key, as well as a distributional checklist of Temnothorax species from mainland China is provided. We suggest that the two new species are likely arboreal based on our collections, however, further arboreal sampling is necessary to confirm this hypothesis. We hope this study may spurn effort to generate further information on sub-tropical Chinese Temnothorax species.